Pengaruh Model Pembelajaran PBL dengan Media PhET Terhadap Hasil Belajar Kognitif Siswa - Nanda Novita; Intan Tri Aulia S; Nuraini Fatmi (Journal on Education, 2023)
This study aims to determine the effect of Problem Based Learning learning model with PhET Simulation media on cognitive learning outcomes on temperature and heat material in class XI MAS Jabal Nur. The type of research is quasi-experimental, the research design is Nonequivalent Control Group Design. The sample was selected by purposive sampling technique, class XI IPA³ as the experimental class and XI IPA¹ as the control class with a total of 28 students. Based on data analysis, the average value of Pretest-Posttest cognitive learning outcomes in the experimental class was 38 and 85.14, while the average value of Pretest-Posttest cognitive learning outcomes in the control class was 38.85 and 76. Hypothesis testing using SPSS-assisted t-test 18.0 obtained a significant value (2-tailed) of 0.000 < 0.05, meaning that is rejected and is accepted. The results of student responses to the Problem Based Learning (PBL) learning model with PhET simulation media were 84% with good criteria. Based on the research, it can be concluded that there is an effect of Problem Based Learning (PBL) learning model with PhET simulation media on cognitive learning outcomes on temperature and heat material in class XI Madrasah Aliyah Swasta Jabal Nur.